Alpha-amylase inhibitors from mycelium of an oyster mushroom - Tamboli E.; Bhatnagar A.; Mishra A. (My University, 2025)
The α-Amylase and α-glucosidase are two main enzymes involved in carbohydrate metabolism. This study was aimed at detecting alpha-amylase inhibitory activity from edible mushroom mycelia. Oyster mushroom was collected from a natural source, from Indian Institute of Technology (Banaras Hindu University) campus and was maintained in vitro in mycelial form. Chloroform, acetone, methanol, and water were used separately for extraction of an active constituent from mycelial cells grown, for 7 days, in potato dextrose broth. The extracts were tested for alpha-amylase inhibitory activity. Chloroform, acetone, and methanol extracts were found to have alpha-amylase inhibitory activity, with IC 50 values of 1.71, 224, and 383 μg/mL, respectively. Aqueous extract had no enzyme inhibitory activity. The acetone extract inhibited α-amylase non-competitively whereas chloroform extract showed competitive inhibition. Acetone extraction yielded highest total phenolic content (TPC) of 0.524 mM of gallic acid equivalent, whereas chloroform extraction resulted in lowest TPC of 0.006 mM. The HPLC and absorbance maxima of acetone and chloroform extracts suggest that the bioactive component responsible for enzyme inhibition could be glycoproteins in chloroform extract and catechins (flavonoids) in acetone extract. Thus, the mushroom mycelia under study may be exploited for production and purification of a lead compound for the development of the α-amylase inhibitory drug. © 2018, © 2018 Taylor & Francis.